EFEKTIFITAS PROGRAM KELUARGA HARAPAN (PKH) DESA TALAN KECAMATAN BANUA LAWAS KABUPATEN TABALONG (p3m.stiatabalong.ac.id, 2022)
The Family Hope Program (PKH) is a program that provides cash assistance to Very Poor Households (RTSM). The Family Hope Program (PKH) is given to Very Poor Households (RTSM) that meet the requirements set by the Ministry of Social Affairs of the Republic of Indonesia based on the Decree of the Coordinating Minister for People's Welfare as chairman of the Poverty Reduction Coordination Team, Number: 31/KEP/MENKO/ -KESRA/IX/2007 concerning